Study on Road Performance and Electrothermal Performance of Poured Conductive Asphalt Concrete - Zhenxia Li; Tengteng Guo; Yuanzhao Chen; Yu Lu; Xiangjie Niu; Xiao Yang; Lihui Jin (Advances in Materials Science and Engineering)
In order to realize the active melting of ice and snow of poured asphalt concrete on steel bridge deck pavement in winter, graphite and carbon fiber were selected as conductive materials to prepare poured conductive asphalt concrete CGA-10. The influence of the content of conductive phase material on the electrical resistivity variation of poured conductive asphalt concrete was studied. The influence of conductive materials and their content on pavement performance of poured conductive asphalt concrete was analyzed. The heating effect of poured conductive asphalt concrete was studied. And the ice melting efficiency of poured conductive asphalt concrete was evaluated by indoor deicing test. Finally, the microstructure characteristics were analyzed by SEM. Experimental results showed: 0.4% carbon fiber +30% graphite can form a good conductive network in poured conductive asphalt concrete. Carbon fiber can make up for the adverse effect of graphite on the pavement performance of poured conductive asphalt concrete. Heating efficiency of 0.4% carbon fiber +30% graphite poured conductive asphalt concrete can reach 78.85%, and its ice melting efficiency can reach 50.03%. Graphite powder particles are tightly wrapped with asphalt mortar, which reduces the porosity and resistivity of asphalt mixture. On the one hand, carbon fiber makes up for the interruption of graphite particle conductive chain, on the other hand, it plays a reinforcing role.